Integrasi Penerapan HACCP dan ISO 9000 dalam Industri Pangan - Sri Raharjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
HACCP (Hazard Analysis Critical Control Point) is a preventive system for assuring the safe production of food product. ISO 9000 refers to a group of international standards containing a specific group of clauses directed at the quality management process of an organisation. The purpose of this paper is to discuss the differences and similarities between HACCP and ISO 9000. Both HACCP and ISO 9000 are fundamental to a process and focus on preventing rather than detecting or correcting a problem. ISO relates to the system, not the product. Food industries should not try to choose either one or the other. Individually they are both exellent programs. Integration of these two can bring the best of both and much more.